Translating Patient-Oriented Eczema Measure (POEM) scores into clinical practice by suggesting severity strata derived using anchor-based methods - Charman, C.R; Venn, A.; Ravenscroft, J.C.; Williams, H.C. (Wiley, 2013)
Background: The Patient-Oriented Eczema Measure (POEM) is a validated, patient-derived assessment measure for monitoring atopic eczema severity, although further information on how different POEM scores translate into disease severity categories is needed for clinical trials, epidemiological research and audit.